Feasibility Analysis and Income Contribution of Banana Mulu Bebe Farming, West Halmahera District - Kaddas, Fatmawati; Ibrahim, Karmila; Baguna, Firlawanti Lestari (Agrikan Jurnal Agribisnis Perikanan, 2023)
Banana "mulu bebe" is an alternative food ingredient that contains carbohydrates other than rice. Problems related to productivity and processing determine the feasibility of business productivity. This research aims to determine the amount of income from "mulu bebe" banana farming on household income in West Halmahera Regency. The research was carried out in West Halmahera Regency, North Maluku Province. The sampling of respondents used a quota-based purposive sampling method with farming feasibility analysis techniques using BCR and RCR indicators as well as the contribution of respondents' household income. The results of the feasibility analysis show that Mulu Bebe banana farming in West Halmahera Regency is feasible and profitable. Based on the results of the feasibility analysis, Mulu banana farming was stated to be profitable because the revenue value was higher compared to the total production costs. Mulu Bebe banana farming in West Halmahera Regency is feasible. This can be seen from BCR (127.94 > 1) and RCR (128.94 > 1). Banana farming can contribute 5,84% of the total income of farmer households. The contribution of banana farmers' income can provide incentives for banana farmers. This condition can increase innovation for farmers in developing other businesses as side businesses. In addition, diversifying businesses and sources of income can reduce banana farmers' dependence and risk of falling banana prices and production.